Using logistic regression to analysis students’ attitudes about e- learning in during COVID- 19 pandemic (case study for students of the Faculty of Science, University of Tabuk) - Fathi, Dalia Kamal; Alharbi, Randa Saleh (Journal of Humanities & Social Sciences, 2021)
The study aimed to use logistic regression to analyze the factors affecting the satisfaction of the students of the University of Tabuk with the e- learning system during COVID- 19 from the perspective of the students themselves to reveal the challenges faced by the students and their satisfaction with the e- learning experience. The study included (321) students at the Faculty of Science, University of Tabuk. The electronic survey method prepared according to the Likert scale was used to collect information related to the study variables. The study adopted the descriptive analytical approach, a logistic regression model was used to determine the factors affecting students’ satisfaction with e- learning.The results of the study showed that the level of student satisfaction with e- learning is good (72%) are satisfied with e- learning. Also, the study found that the course material prepared, speed of internet, assessment, and Workshops and explanations prepared by the Deanship of E- Learning to help students had a significant positive effect on student satisfaction. The study recommends the necessity of measuring student satisfaction on a continuous basis to improve and develop the educational process.